2013
DOI: 10.1593/tlo.13271
|View full text |Cite
|
Sign up to set email alerts
|

Individual Profiling of Circulating Tumor Cell Composition and Therapeutic Outcome in Patients with Hepatocellular Carcinoma

Abstract: Our data suggest that different CTC populations are identifiable in peripheral blood of HCC patients and, for the first time in HCC, that these individual cell type profiles may have distinct clinical implications. The further characterization and analysis of patients in this ongoing study seems to be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…In another study, CTCs were found in 28% of HCC patient samples analysed with the CellSearch system but in 100% of samples analysed with an EpCAM-independent filtration method. 43 In a third study, multiimmunofluorescence identified considerable heterogeneity within CTC populations in HCC patients 44 and changes in the ratio of epithelial to mesenchymal cells were associated with a longer time to disease progression.…”
Section: Tumor Markers and Signaturesmentioning
confidence: 97%
“…In another study, CTCs were found in 28% of HCC patient samples analysed with the CellSearch system but in 100% of samples analysed with an EpCAM-independent filtration method. 43 In a third study, multiimmunofluorescence identified considerable heterogeneity within CTC populations in HCC patients 44 and changes in the ratio of epithelial to mesenchymal cells were associated with a longer time to disease progression.…”
Section: Tumor Markers and Signaturesmentioning
confidence: 97%
“…Because only 20%‐35% of HCCs express EpCAM, methods based on EpCAM alone have resulted in low CTC detection rates and limited utility for HCC . Alternative CTC capture methods using antibodies directed at hepatocyte‐specific cell surface markers, CD45 depletion, or microfluidic systems have all demonstrated increased efficiency in isolating HCC CTCs. Furthermore, these non‐EpCAM–based methods allow for the capture of distinct CTC subpopulations with more mesenchymal properties in HCC …”
mentioning
confidence: 99%
“…Numerous devices were developed on the basis of this characteristics and collect cells with larger size (often >15 μm), including dielectrophoresis (DEP) [43,44], optically induced dielectrophorestic (ODEP) [45] force-dependent devices, and filter-based systems [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. However, other investigators found that the size of real CTCs could be greatly differed from cell lines [62], and might even vary interindividually and intraindividually [63,64]. The size criteria of CTC definition remain in debate.…”
Section: Natures Of Ctcsmentioning
confidence: 99%